Corn residue baling and grazing impacts on corn yield under irrigated conservation tillage systems. (14th April 2021) - Ruis, Sabrina J.; Burr, Charles; Blanco‐Canqui, Humberto; Olson, Brian; Reiman, Mark; Rudnick, Daran; Baller, Johnna; Hanford, Kathryn
Abstract: Crop residue grazing or baling is common in the western Corn Belt. However, its impacts on subsequent crop yields under different irrigation levels and tillage systems are unclear. We investigated the impacts of corn ( Zea mays L.) residue baling and cattle grazing on soil compaction, water content, and corn yield under full and limited irrigated no‐till in Nebraska during three years. In Years 2 and 3, an additional tillage treatment (strip till) was implemented to evaluate its effects on grain yield under the above treatments. Residue removal effects on compaction and water content did not vary with irrigation level. Grazing (3.68 animal units ha −1 ) minimally impacted compaction and soil profile water content compared to no removal. Baling increased cone index by 34–53% in the 0‐to‐12.5‐cm depth and decreased water content by 6 cm compared to no removal. Residue removal effects on yield did not depend on irrigation. Residue removal impacts depended on tillage in Year 3 only. Full irrigation increased corn yields up to 11% compared to limited irrigation. Strip till increased yield by 11% compared to no‐till in Year 2 only. Baling and grazing had no effect on corn yield in Year 1, but baling and grazing increased yield by 9% compared to no removal in Year 2, likely due to lower water content. In Year 3, grazing and baling increased yield by 9% under no‐till but not strip till. Overall, grazing had minimal impacts while baling increased yield and compaction and decreased water content with few variations due to irrigation or tillage. Core Ideas: Corn residue removal effects on compaction were small and below threshold to restrict root growth. Baling, unlike grazing, reduced soil water content in 1 of 2 yr compared to no removal. Baling and grazing increased corn yield in 2 of 3 yr. Limited irrigation reduced yield compared to full while strip till increased yield compared to no‐till. Residue removal effects rarely varied with irrigation or tillage.